Groundwater quality at Achiase and Wabiri in the Ejisu Juaben municipality of the Ashanti region in Ghana - B.M. Tiimub; S. Frimpong; R.A. Kuffour; A.B. Dwumfour; I. Monney; K. Obiri-Danso (International Journal of Development and Sustainability, 2012)
Groundwater from one well and one borehole from Wabiri and Achiase in the Ejisu-Juaben community in Ashanti Region of Ghana was analyzed from January to December, 2011for its physical, chemical and biological quality characteristics using various standard methods. Bacterial in wells ranged between 1.0 × 102 - 2.42 × 102, 1.0 × 101 – 2.0 × 100 and 4.6 × 101 - 8.4 × 101 for total coliforms, E. coli and salmonella, but was absent from borehole waters. There were highly significant differences (P < 0.000 and P < 0.000) between the entire well and borehole waters. BOD5 levels of the wells ranged from 1.05 ± 0.00mg/L - 1.35 ± 2.75mg/L while it was 0.9 ± 0.00mg/L in the boreholes throughout the study. Traces of chemicals were found in the well and borehole waters, but their concentrations:- iron (0.036 ± 0.01mg/L - 0.07 ± 0.57mg/L and 0.01 ± 0.00); nitrate (0.11± 0.0001mg/L - 0.17 ± 0.001mg/L and 0.03 ± 0.0005 - 0.05 ± 0.001); nitrite (0.005 ± 0.001mg/L - 0.008 ± 0.001mg/L and 0.001 ± 0.00mg/L - 0.013 ± 0.001mg/L, and chloride (15.6 ± 1.16mg/L - 18.33 ± 0.58mg/L and 27.65 ± 1.16mg/L – 38.33 ± 0.56mg/L) were within the WHO Guidelines. Water from the borehole was generally of higher quality than the well and so the latter water must be subjected to treatment such as filtration, chlorination and boiling before drinking.